A hydrostable Zn2+ coordination polymer for multifunctional detection of inorganic and organic contaminants in water. Issue 44 (20th October 2021) - Cheng, Hao; Song, Fu-Qiang; Zhao, Na-Na; Song, Xue-Qin
Abstract : A water-stable and highly emissive Zn 2+ coordination polymer together with its PMMA films was developed for sensing of Fe 3+ and picric acid (PA) in water. Abstract : From the perspective of human health and environmental safety, the development of hydrostable fluorescent sensors for the detection of heavy metal ions and nitroaromatics is an important but a challenging issue. To this end, a water-stable Zn 2+ coordination polymer formulated as [Zn(H2 L)]·2DMF·3H2 O n (ZnCP ) was prepared elaborately by a solvothermal method using a multidentate ligand (H4 L) with 2, 6-pyridine-dicarboxylic acid spaced by para -substituted benzene. Single-crystal analysis shows that the new ZnCP exhibits one-dimensional chain structural features, which further promoted to afford a wrinkled two-dimensional network structure via inter-chain hydrogen bonding. Powder X-ray diffraction and fluorescence measurements show that it can maintain crystallinity and structural integrity under harsh acidic and alkaline conditions with the pH ranging from 4 to 11. Notably, the bright blue–emissive ZnCP showed selective fluorescence quenching effects for Fe 3+ and picric acid (PA), which makes it an excellent chemical sensor for Fe 3+ and picric acid (PA) with low detection limits of 0.41 and 0.26 μM in water. The recognition mechanism of Fe 3+ could be attributed to UV absorption competition and resonance energy transfer in the aid of weak electrostatic interactions, while the recognition mechanism of PA is considered to be a multi-quenching mechanism dominated by absorption competition and PET effects with the assistance of hydrogen bonding. In addition, poly(methyl methacrylate) (PMMA) films doped with ZnCP (ZnCP @PMMA) were developed to provide better sensing performance and portability for practical applications.